Peran Gender dan Education dalam Membentuk Entrepreneurial Orientation pada Pelaku UKM - Indah Yani; Dara Alifa Fajriati Thamrin; Leny Marlina (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This research analyze whether entrepreneurial orientation (EO) in the Small and Medium Enterprises (SMEs) depends on the level of education and gender, in the face of inconsistencies between theoretical assumptions and available empirical evidence. The design of this study was a survey of 126 purposely selected SME owners in Indonesia, a quantitative approach. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data and determine the relationship between variables. The findings indicate that education level positively and significantly impacts EO and there is no significant impact of gender. The result implies that cognitive capacity and access to knowledge have a greater impact on entrepreneurial orientation than the demographic attributes based on gender. The novelty of the present study can be seen in its critical point of view at revisiting the role of gender as a social construction in models of entrepreneurship and identifying discrepancies in the nature of the relationship between education and EO in the case of SMEs in Indonesia. The contribution of this study to the literature on entrepreneurship is that the contextual and non-demographic factors are important in explaining differences in entrepreneurial orientation and that the study offers a concrete foundation to the formulation of more extensive follow-up studies.